Review of nonpharmacological interventions for delaying the effects of cerebral neuropathy caused by diabetes - Lee, Chi; Lai, Chien-Wen; Wu, Guan-Lin; Yen, Shaoyu; Huang, Chih-Mao; Liu, Zong-Hsin; Hu, Po-Chi; Liao, Lun-De (Frontiers in Endocrinology, 2025)
Diabetic peripheral neuropathy (DPN) is a debilitating complication of diabetes that affects nearly half of diabetic patients and manifests as chronic pain, sensory loss, and motor dysfunction. The limited efficacy of traditional pharmacological treatments, coupled with their side effects, has intensified the search for alternative therapies that not only mitigate symptoms but also delay the progression of diabetes-related neural complications. In this review, the potential of transcranial magnetic stimulation (TMS) as a nonpharmacological intervention for DPN is explored, with a focus on the ability of TMS to delay neural inflammation—a key factor in the progression of DPN—rather than directly treating diabetes. TMS has shown promising results in alleviating neuropathic pain, promoting nerve regeneration, and regulating autonomic nervous function, making it a strong candidate for delaying adverse neural outcomes. Other neuromodulation techniques, such as spinal cord stimulation (SCS), decompression nerve surgery (DNS), and transcranial direct current stimulation (tDCS), have also been examined for their efficacy in treating DPN. While TMS has significant therapeutic potential for protecting neural function and delaying inflammation, further research is needed to optimize treatment protocols and understand their long-term benefits. This review emphasizes the translational potential of neuromodulation technologies in delaying the progression of diabetes-induced neural damage, underscoring the need for further studies to translate these therapies into clinical practice.